2004
DOI: 10.4314/wsa.v27i2.4999
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages: update on application as models for viruses in water

Abstract: Phages are valuable models or surrogates for enteric viruses because they share many fundamental properties and features. Among these are structure, composition, morphology, size and site of replication. Even though they use different host cells, coliphages and Bacteroides fragilis phages predominantly replicate in the gastro-intestinal tract of humans and warm-blooded animals where enteric viruses also replicate. A major advantage of phages is that, compared to viruses, they are detectable by simple, inexpens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
232
1
29

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(269 citation statements)
references
References 157 publications
(84 reference statements)
7
232
1
29
Order By: Relevance
“…Somatic and FRNA coliphages can be relied on because they are relatively simple and can be detected rapidly. Moreover, they are always present in the faeces of many warm-blooded animals as indicators of faecal pollution, when compared to bacteria (Grabow 2001). This study was designed to evaluate the general efficiency of sedimentation (after coagulation/flocculation) and filtration processes used prior to the chlorination of the final water in the Temba, Klipdrift and Wallmannsthal WTPs in the removal of viral indicators (somatic and FRNA coliphages) and to determine the source of faecal pollution with a view to water source management.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Somatic and FRNA coliphages can be relied on because they are relatively simple and can be detected rapidly. Moreover, they are always present in the faeces of many warm-blooded animals as indicators of faecal pollution, when compared to bacteria (Grabow 2001). This study was designed to evaluate the general efficiency of sedimentation (after coagulation/flocculation) and filtration processes used prior to the chlorination of the final water in the Temba, Klipdrift and Wallmannsthal WTPs in the removal of viral indicators (somatic and FRNA coliphages) and to determine the source of faecal pollution with a view to water source management.…”
Section: Resultsmentioning
confidence: 99%
“…This would result in a substantial reduction in turbidity at each stage. The effectiveness of virus removal during water treatment may also be affected by factors that act against particle association (floc formation), such as pH and temperature conditions (Grabow 2001;LeChevelier and Au 2004). Although, on average, the pH values recorded were within the recommended limits (pH 6-9), there were maximum values of 9.50 and 9.78 in settled water and of 9.41 and 9.62 in water samples collected after filtration from Temba and Klipdrift, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FRNA coliphages proliferate in the gastrointestinal tract of warmblooded animals, are shed exclusively in feces and loosely display similar sensitivities to several chemical and environmental stresses in comparison to enteric viruses (Grabow, 2001;Havelaar et al, 1993). It has also been demonstrated that FRNA coliphages are indicative of the presence and persistence of human enteric viruses in various water types and shellfish (Bae and Schwab, 2008;Doré et al, 2000;Havelaar et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple strategies have been developed to concentrate viruses from water, including electronegative and electropositive filters (Ikner et al, 2012). However, these filters are prone to clogging, viral elution is achieved in relatively large volumes (10 ml to 300 ml) adding undesirable dilution effects and elution buffers are often of extreme pH or protein content which may limit downstream detection (Grabow, 2001;Ikner et al, 2012;Paar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%